Kanon MELAYU - Norazimah Zakaria (BANGI : PENERBIT UNIVERSITI KEBANGSAAN MALAYSIA, 2017)
On history and criticism of epic Malay literature
Includes index
Bibliography: pages [229]-238
Keywords: Epic literature, Malay -- History and criticism; Malay literature -- To 1900 -- History and criticism; Malay literature -- History and criticism; Malay literature -- Criticism, Textual